Posthuman Art: The Structural Production of Space - Akdeniz, Lütfi (Erzurum Teknik Üniversitesi, 2025)
Objective: This study aims to analyze the ontological, aesthetic, and technological transformation of art by examining the structural production of space within the framework of a posthumanist understanding of art. Posthumanism transcends the anthropocentric classical humanist paradigm and offers an approach that acknowledges non-human actors—technology, artificial intelligence, materials, and environmental elements—as productive partners in art. In this context, the study discusses how space is positioned not as a passive surface in art production, but as a dynamic cognitive organism where subjectivity is produced, redistributed, and continuously transformed through technological-biological interactions. The theoretical framework draws on Andrea Barcaro's nomadic subjectivity and postcolonial body politics, the posthuman utopias of Iglesias Garcia and Paniotova, Tronca's kinetic analyses of the body-space relationship, and the posthumanist approaches of thinkers such as Rosi Braidotti, N. Katherine Hayles, Donna Haraway, and Karen Barad. Methods: Qualitative method was used in the research; document analysis, case study and theoretical discourse analysis techniques were carried out together. Results: The findings demonstrate that posthumanist art redefines space as a data-driven, interactive, and productive system, transcending its mere display surface. Refik Anadol's approach to data aesthetics is then linked to Walter Benjamin's concept of "loss of aura" and evaluated within the framework of technological reproduction, virtual space, and the aesthetics of experience. Conclusion: Ultimately, posthuman art blurs the boundaries between subject and object, revealing that space becomes an active subject in aesthetic, ethical, and cognitive dimensions. This set of values presents a comprehensive transformation in contemporary art practice, redefining both the function of space and the existential position of the human.

Amaç: Bu çalışma, insan-sonrası (posthümanist) sanat anlayışı çerçevesinde mekânın yapısal üretimini inceleyerek, sanatın ontolojik, estetik ve teknolojik dönüşümünü analiz etmeyi amaçlamaktadır. Posthümanizm, insan merkezli klasik hümanist paradigmayı aşarak, insan-dışı aktörleri—teknoloji, yapay zekâ, malzeme ve çevresel unsurları—sanatın üretken ortakları olarak kabul eden bir yaklaşım sunar. Bu bağlamda çalışma, mekânın sanat üretiminde edilgen bir yüzey olarak değil, öznelliğin üretildiği, yeniden dağıtıldığı ve teknolojik-biyolojik etkileşimlerle sürekli dönüştürüldüğü dinamik bir bilişsel organizma olarak nasıl konumlandığını tartışmaktadır. Kuramsal çerçeve; Andrea Barcaro’nun nomadik öznelik ve postkolonyal beden politikaları, Iglesias Garcia ve Paniotova’nın posthüman ütopyaları, Tronca’nın beden–mekân ilişkisine dair kinetik analizleri ile Rosi Braidotti, N. Katherine Hayles, Donna Haraway ve Karen Barad gibi düşünürlerin posthümanist yaklaşımlarına dayanmaktadır. Yöntemler: Araştırmada nitel yöntem kullanılmış; doküman analizi, örnek olay incelemesi ve kuramsal söylem çözümlemesi teknikleri bir arada yürütülmüştür. Bulgular: Bulgular, posthümanist sanatın mekânı yalnızca sergileme yüzeyi olmaktan çıkararak, veriye dayalı, etkileşimli ve üretken bir sistem olarak yeniden tanımladığını göstermektedir. Bu doğrultuda Refik Anadol’un veri estetiği yaklaşımı, Walter Benjamin’in “auranın kaybı” kavramıyla ilişkilendirilerek teknolojik yeniden üretim, sanal mekân ve deneyim estetiği ekseninde değerlendirilmiştir. Sonuç: Sonuç olarak, insan-sonrası sanat, özne ile nesne arasındaki sınırları bulanıklaştırarak mekânın estetik, etik ve bilişsel boyutlarda aktif bir özneye dönüştüğünü ortaya koymaktadır. Bu değerler dizisi, çağdaş sanat pratiğinde hem mekânın işlevini hem de insanın varoluşsal konumunu yeniden tanımlayan kapsamlı bir dönüşüm sunmaktadır.
İnsan Sonrası Sanat: Mekânın Yapısal Üretimi
Keywords: Art Sociology; Sanat Sosyolojisi